Fishes of the South China Sea - Kyushin, Kenichiro; Amaoka, Kunio; Nakaya, Kazuhiro; Ida, Hitoshi; Tanino, Yasuo; Senta, Tetsushi (Japan Marine Fishery Resource Research Center, 1982)
Text in English and Japanese